Development Of Analytical Observation Abilities In Students As A Public-Pedagogical Necessity - Arzieva Surayyo Ismatullaevna (Zien Journals, 2024)
In this article, the development of analytical observation skills in students is studied as a socio-pedagogical necessity. Also, consistent and thorough opinions were given that in the current period, young people are given enough opportunities to apply their professional knowledge in life, and that the provision of this task can raise the quality of education to a high level
Keywords: Pedagogy; education; technology; ability